PERFORMANCE ALAT PENGUPAS KENTANG DALAM MENINGKATKAN PRODUKTIVITAS KERIPIK KENTANG PAKUWOJO DI WONOSOBO - Edy Supriyo; Isti Pujihastuti; Ireng Sigit Atmanto (Universitas Muhammadiyah Semarang, 2018)
Potato crackers is one prime product of Wonosobo Regency, aside from carica and purwaceng. One of potato crackers producers is UMKM Pakuwojo with brand of Pakuwojo. The demand of potato crackers is increasing form time to time. The problems faced by industry is peeling potato which done manually, so that need more time and labour. Therefore they need simple technology to increase their productivity, i.e. potato peeler machine. The machine is designed having capacity of 60 kg/hour, 150 rpm with power of 0,5 HP, equiped with water sprayer so the product has laready clean. The experiment to test the machine performance is used potato grade A and B. The result showed that in UMKM Paku Wojo, the machine performance is good having 150 rpm with capacity of 60 kg/hour. When it is operated for 50-60 minutes, the potato skin was 97,50% cleaned and losing weight of 1,5%. Keywords: potato peeler machine, performance, crackers